Commodifiaction Of Workers On Esports Athletes In Digital Sports Industry - Anshari, Faridhian; Evangelina, Jane; Abbabil, Syafira U.F.T (Jurnal Komunikasi, 2022)
The Esports industry has begun to produce various media platforms that display interesting game content played by athletes, to attract viewers to join the platform through live streaming. The purpose of this study is to analyze the meaning of commodification of workers from the athlete's perspective, who are already involved as commodities. The expected benefits are recommendations to minimize the forms of commodification such as exploitation of workers. This study uses a review of media political economy theory that is associated with the movement of the esports industry ecosystem. The approach used in this research is qualitative by using a descriptive study. The data collection technique uses an in-depth interview method with esports athletes, virtual observation, and collecting documents. The findings are that esports athletes consciously feel that their identity as an athlete becomes a commodity that has a selling value to agencies and other actors in the digital sports industry. However, the good income and not being seriously regulated, allows them to reach as much profit as possible, although there are still revenue cuts from the agency. This profit also changes their early goals and mindset as esports athletes, from being a games players and start thinking about profit even though they realize are being exploited. The finding is the athlete's ability to conjure up their role as a commodity in the industry, by utilizing the athlete's identity as a valueable commodity for their own benefit.